2021
DOI: 10.1016/j.isci.2021.102497
|View full text |Cite
|
Sign up to set email alerts
|

Striatal dopamine synthesis capacity reflects smartphone social activity

Abstract: Summary Striatal dopamine and smartphone behavior have both been linked with behavioral variability. Here, we leverage day-to-day logs of natural, unconstrained smartphone behavior and establish a correlation between a measure of smartphone social activity previously linked with behavioral variability and a measure of striatal dopamine synthesis capacity using [ 18 F]-DOPA PET in (N = 22) healthy adult humans. Specifically, we find that a higher proportion of social app intera… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…Critically, the absence of correlations was not due to measurement error in the estimates of striatal dopamine synthesis capacity or a lack of behavioural relevance of these estimates. The striatal [ 18 F]-FDOPA uptake values are in the typical range (Supplementary Figure S1), and dopamine synthesis capacity in this dataset has been shown to account for (dopamine drug effects on) effort-based decision making, response vigour, reversal learning, and smartphone social activity in the expected direction (Hofmans et al, 2020(Hofmans et al, , 2022Westbrook et al, 2020Westbrook et al, , 2021. More specifically, [ 18 F]-FDOPA uptake in the striatum was associated positively with the value of cognitive effort (Westbrook et al, 2020), with the impact of average reward value on response vigour (Hofmans et al, 2022) and with dopaminergic drug-related changes in prediction errorrelated BOLD signal in the striatum (van den .…”
Section: Discussionmentioning
confidence: 82%
“…Critically, the absence of correlations was not due to measurement error in the estimates of striatal dopamine synthesis capacity or a lack of behavioural relevance of these estimates. The striatal [ 18 F]-FDOPA uptake values are in the typical range (Supplementary Figure S1), and dopamine synthesis capacity in this dataset has been shown to account for (dopamine drug effects on) effort-based decision making, response vigour, reversal learning, and smartphone social activity in the expected direction (Hofmans et al, 2020(Hofmans et al, , 2022Westbrook et al, 2020Westbrook et al, , 2021. More specifically, [ 18 F]-FDOPA uptake in the striatum was associated positively with the value of cognitive effort (Westbrook et al, 2020), with the impact of average reward value on response vigour (Hofmans et al, 2022) and with dopaminergic drug-related changes in prediction errorrelated BOLD signal in the striatum (van den .…”
Section: Discussionmentioning
confidence: 82%
“…Recent years have shown that this is possible. For instance, digital footprints recorded from smartphones could already be linked to molecular genetics, MRI or PET data footprints ( 28 , 40 , 41 ), but it is also true that the findings from these studies present correlations and to infer causality in such variable sets will be a tremendous task for several years. Hence, before digital biomarkers (hence patterns of digital footprints) alone can be seen as real surrogates for a biological outcome, sophisticated research plans need to be followed and the Clinical Trials Transformation Initiative in June 2017 has made some recommendations to reach such an ambitious goal.…”
Section: Discussion: Researchers Should Make Clearer In Abstracts and Titles What They Investigatementioning
confidence: 99%
“…Additionally, PET data of two other participants were incomplete (one due to scanner software issues and another due to discomfort during scanning). Participants could choose to take part in two additional, but not required, parts of the study; submit a saliva sample for genetic dopamine pathway analysis (via the Cognomics project already running at the center) and/or consent to a passive collection of coarse measures of smartphone use (Westbrook, Ghosh, van den Bosch, Määttä, Hofmans & Cools, 2021). There were 18 and 29 participants out of the 100 participants that agreed to take part in these respective projects.…”
Section: Samplementioning
confidence: 99%
“…Between the last pharmaco-fMRI session and the [ 18 F]DOPA PET session participants received an online package of questionnaires to be filled out at home (off drug) to acquire additional baseline measures, such as trait impulsivity (Patton, Stanford, & Barratt, 1995), behavioural activation/inhibition (Franken, Muris, & Rassin, 2005, Carver & White, 1994, need for cognition (Cacioppo, Petty, & Kao, 1984), creativity (Kaufman, 2012), and depression (Beck et al, 1996). As an additional part of the study procedure participants could allow passive collection of coarse measures of smartphone use during a three-week period, to assess the relation between dopamine and social media app use (Westbrook, Ghosh, van den Bosch, Määttä, Hofmans & Cools, 2021).…”
Section: Daymentioning
confidence: 99%